Measurement of hydraulic properties of growing media with the HYPROP system - Schindler Uwe; Thielicke Matthias; Saljnikov Elmira; Zivotić Ljubomir; Eulenstein Frank (Zemljište i biljka, 2022)
Knowledge of hydro-physical properties is an essential prerequisite for assessing the suitability and quality of growing media. The method used for sample preparation is important for the measurement results. Three different sample preparation methods were compared. The methods differed in terms of the way the 250°cm3 steel cylinder was filled and the height of preloading. Measurements on loosely filled cylinders were included. The comparison was carried out on 15 growing media using the HYPROP device. HYPROP enables a complex analysis of the hydro-physical properties with high accuracy and reproducibility. The water retention curve, the unsaturated hydraulic conductivity function, the dry bulk density, the shrinkage and the rewetting properties can be measured simultaneously. The air capacity and the amount of plant-available water in pots depend on the height of the pot. In the field, it is related to the field capacity. The quality assessment was carried out both for flowerpots of different height and for field conditions with free drainage. Loosely filled samples consolidated hydraulically shortly after the start of the measurement. These geometric changes can be taken into account with the HYPROP. The sample preparation method - preloading or loose filling - yielded significantly different results for the pore volume, dry bulk density, plant available water and air capacity. The total pore volume of the loosely filled cylinders varied between 86.8 and 95.2°% by vol. (preloaded 81.3 and 87.7°% by vol.). The most critical factor was the air capacity. Loosely filled substrate samples achieved the highest air capacities, but also did not reach the critical value of 10°% by volume in shallow flowerpots, e.g. in 10 cm pots with 5.8°% by volume. The sample preparation method, measurement and quality assessment of the hydro-physical properties of growing media should be adapted to the conditions of use - whether they are used in a field with free drainage or in pots or containers in greenhouses.